It's the way people move! Labour migration as an adjustment device in Russia - Francesco Pastore; Elena Semerikova (Global Labor Organization (GLO), 2020)
This paper aims to assess the role of migration as an adjustment mechanism device to favor convergence across states and regions of Russia. In contrast to previous studies, we use variations in the population of a region as a proxy of its net migration rate and apply spatial econometric methodology in order to distinguish the effect from the neighbouring regions. We provide descriptive statistical evidence showing that Russia has more/less/the same intense migration flows than the USA and EU. The econometric analysis shows that migration flows are sensitive to both regional income and regional unemployment differentials. Nonetheless, we find that internal migration is sensitive to regional unemployment and income differentials of neighbouring regions. Dependent on the welfare, pre- or after-crisis period, income in neighbouring regions can create out- or in-migration flows. The relatively high degree of internal mobility coupled with the low sensitivity of migration flows to the local unemployment rate of distant regions might explain why migration flows tends not to generate convergence, but rather divergence across Russian regions.
Keywords: F15; F22; J61; R23; 330; Internal and International migration; Adjustment mechanism; spatial econometrics; Russia